2016
DOI: 10.1017/s0960258516000155
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the terminal velocity of tiny diaspores

Abstract: Although it has long been acknowledged that seed characteristics are of major importance to the conquest of tree crowns by vascular epiphytes, there is surprisingly little quantitative evidence on the aerodynamic properties of their diaspores. We used a custom-built device to determine the terminal velocity (Vterm) of falling seeds, a parameter that has been shown to have high predictive power for the wind dispersal potential of diaspores under natural conditions. We determined Vterm of 45 species of epiphytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…Terminal velocity might be an important indirect parameter for predicting the capacity of diaspores for secondary dispersal by wind, since it is thought to be linked to dispersal distance ( Andersen, 1992 ; Tackenberg, 2003 ; Soons et al , 2004 ; Nathan et al , 2011 ; Caplat et al , 2012 ; Zotz et al , 2016 ). In our study, terminal velocity was correlated to lift-off velocity for all species only on the upwind slope and in species with diaspore appendages on both slope directions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terminal velocity might be an important indirect parameter for predicting the capacity of diaspores for secondary dispersal by wind, since it is thought to be linked to dispersal distance ( Andersen, 1992 ; Tackenberg, 2003 ; Soons et al , 2004 ; Nathan et al , 2011 ; Caplat et al , 2012 ; Zotz et al , 2016 ). In our study, terminal velocity was correlated to lift-off velocity for all species only on the upwind slope and in species with diaspore appendages on both slope directions.…”
Section: Discussionmentioning
confidence: 99%
“…where m is the diaspore mass and p is the projected area. The terminal velocity was defined as the constant falling velocity of a diaspore in still air ( Green, 1980 ), and it was measured with an apparatus described by Zotz et al (2016) .…”
Section: Methodsmentioning
confidence: 99%
“…a lower settling velocity (0.06 m/s) than orchid seeds (0.09-0.4), enhancing long-distance wind dispersal (Zotz et al, 2016). Analyses of population genetic structure in tropical epiphytic ferns further revealed that most of the genetic diversity was distributed within populations and failed to evidence any significant clustering, pointing to strong migration rates among populations (Winkler et al, 2011).…”
Section: Randomized Occupancy Rate (Mean ± Sd)mentioning
confidence: 99%
“…Wing loading is diaspore mass divided by projected area (Greene and Johnson, 1997). The terminal velocity was measured with an apparatus (a black lightproof box provides a calm space for the determination of the falling velocity) described by Zotz et al (2016). The constant falling velocity of a diaspore in still air was recorded by a camera (Zhou et al, 2020).…”
Section: Diaspore Selection and Trait Measurementsmentioning
confidence: 99%